TATA AKADEMIK MAHASISWA TERHADAP DOSEN PEMBIMBIN STUDI ETIKA DAN KOMUNIKASI AKADEMIK DI PERGURUAN TINGGI - Ataina Zulfa Nasution; Allia Rosintan Siregar; Indah Amelia; Muhammad Dzikry Falah Erlangga; Nia Rahmadani; Rolan Rizki Rinaldi Daulay (CV. Arsy Persada Quality, 2025)
Academic relations between students and supervisors are crucial elements in supporting the success of final assignments in higher education. However, in practice, there is still a mismatch between the expected academic norms and student behavior in the guidance process. This study aims to examine the understanding and application of academic rules by students, with a focus on aspects of communication, discipline, and scientific responsibility. This study uses a qualitative descriptive approach through literature studies and descriptive observations. The results show that many students have not applied academic ethics consistently, reflected in the use of informal language in communication, absence without confirmation, and lack of initiative in completing revisions. This indicates weak internalization of academic values and minimal systematic guidance since the beginning of the study. These findings emphasize the need for ongoing institutional intervention through the integration of academic ethics in orientation programs, scientific communication training, and the preparation of applicable guidance guidelines. These efforts are expected to build an ethical, professional academic culture and support the success of student studies holistically..